VMware horizon workspace essentials : manage and deliver a secure, unified workspace to embrace any time, any place, anywhere access to corporate apps, data, and virtual desktops securely from any device /: manage and deliver a secure, unified workspace to embrace any time, any place, anywhere access to corporate apps, data, and virtual desktops securely from any device. (2014) - Von Oven, Peter; Björk, Peter; Lindberg Joel
No abstract available